(untitled) - Till, Steven (Clifton Park, N.Y., 2006)
In his previous book, author Steven Till introduced the core 3D concepts of object modeling, texturing, and rendering. In this new companion book, Till shows how to "set things in motion" - moving beyond static models and renderings and bringing characters and objects to life. Throughout the book, a rich combination of text and illustrations shows how to execute concepts using Autodesk’s widely used 3ds max animation program, with the focus always on "the art of animation." Step-by-step project walk-throughs in media animation and forensic animation, among others, round out this often-entertaining and always-instructive resource
Keywords: Computer animation,Computer graphics,Đồ họa vi tính